Proliferation, Migration, and Expression of Tumor Necrosis Factor-α from Green Tea Leaf Extract (Camellia sinensis) on Keloid Fibroblast Cells: Proliferasi, Migrasi, dan Ekspresi Tumor Necrosis Factor-α Ekstrak Daun Teh Hijau (Camellia sinensis) pada Sel Fibroblas Keloid - Dewi, Lia Sari Utami; Hadi, Restu Syamsul; Eliana, Fatimah; Hakim, Jasir (Universitas Muhammadiyah Sidoarjo, 2025)
Keloid is a fibroproliferative dermal disorder caused by abnormal wound healing, characterized by excessive collagen deposition that extends beyond the wound boundaries. Keloids can cause pruritus and even pain. In addition to these two issues, keloids also diminish a person's quality of life due to aesthetic problems, especially if they appear on the face or other visible areas of the skin. Combination treatments for keloids are usually more successful than single treatments. Green tea leaf extract contains epigallocatechin-3-gallate polyphenols as anti-inflammatory agents. The aim of this study is to determine the potential of green tea leaf extract by observing the proliferation, migration, and expression of TNF-α in keloid fibroblast cells. Keloid fibroblast cells were divided into five treatment groups (TH100, TH200, TH400, TH800, and DEX100) and one negative control (DS). Cell proliferation was tested using a cell counting kit-8, migration was assessed using a scratch assay, and TNF-α expression was measured using an ELISA kit. All data were analyzed using SPSS, performing One-Way ANOVA, followed by Kruskal Wallis and Mann Whitney tests. The results showed that green tea leaf extract at a dose of 800 μg/mL significantly reduced the proliferation and migration rate of keloid fibroblast cells (p < 0.05). Meanwhile, in the TNF-α expression test, no significant difference was found in reducing TNF-α expression levels in keloid fibroblast cells (p > 0.05). Green tea leaf extract has the potential to be used as an alternative treatment for keloids as it reduces the proliferation and migration of keloid fibroblast cells.